2013
DOI: 10.1108/02656711311315512
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic systems approach to weight related health problems

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Additionally, the improvement of chronic diseases has been investigated by implementing different interventions, such as increasing access to primary care [ 86 ], evaluating the behavior of cardiovascular drugs on the market [ 87 ], increasing income and employment, enhancing social cohesion and neighborhood attractiveness [ 88 ], and improving physician education and care coordination [ 89 ]. Mehrjerdi [ 90 ] analyzed the interconnections between health problems and weight, and found that teaching individuals about their health will have a considerable impact on the number of deaths from heart attacks.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the improvement of chronic diseases has been investigated by implementing different interventions, such as increasing access to primary care [ 86 ], evaluating the behavior of cardiovascular drugs on the market [ 87 ], increasing income and employment, enhancing social cohesion and neighborhood attractiveness [ 88 ], and improving physician education and care coordination [ 89 ]. Mehrjerdi [ 90 ] analyzed the interconnections between health problems and weight, and found that teaching individuals about their health will have a considerable impact on the number of deaths from heart attacks.…”
Section: Discussionmentioning
confidence: 99%
“…Kiani et al (2009) used an SD model for analyzing the influence of costs of quality. Mehrjerdi (2012) demonstrated the use of systems thinking for health care management. Williams (2000) used an SD model to quantify the effects of changes in safety regulations through two case studies.…”
Section: Methodsmentioning
confidence: 99%
“…In system dynamics (SD), several models describe the behavior of the nonlinear dynamic structures present in the human body (Abdel-Hamid, 2002;Hosseinichimeh et al, 2015;Hsieh et al, 1990;Karanfil and Barlas, 2008;Lee et al, 2016;Mehrjerdi, 2013). In Rogers et al (2018), a SD model of erythropoiesis was developed and calibrated in renal patients with anemia by establishing a personalized EPO dosage to stabilize hemoglobin levels.…”
Section: Introductionmentioning
confidence: 99%
“…In system dynamics (SD), several models describe the behavior of the nonlinear dynamic structures present in the human body (Abdel‐Hamid, 2002; Hosseinichimeh et al ., 2015; Hsieh et al ., 1990; Karanfil and Barlas, 2008; Lee et al ., 2016; Mehrjerdi, 2013). In Rogers et al .…”
Section: Introductionmentioning
confidence: 99%